Comparative study of CURB-65, Pneumonia Severity Index and IDSA/ATS scoring systems in community acquired pneumonia in an Indian tertiary care setting - Madhu, S.; Augustine, Sabu; Ravi Kumar, Y. S.; Kauser M. M., Kauser; Kumar, S. R. Vagesh; Jayaraju, B. S. (International Journal of Advances in Medicine, 2017)
Background: Few comparative studies regarding prognostic scoring systems for community acquired pneumonia (CAP) are available from Indian context. Methods: Hospital-based prospective study to test the comparison between confusion, urea, respiratory rate, blood pressure, age over 65 years (CURB-65), Pneumonia severity index (PSI) and infectious diseases society of America/American thoracic society criteria (IDSA/ATS) scoring systems in patients with community acquired pneumonia. Results: CURB-65 class ≥III, PSI class ≥IV and patients who needed admission to intensive care unit (ICU) based on IDSA/ATS criteria were having sensitivity of 41.7%, 91.7% and 87.5% in predicting ICU admission with a specificity of 89.5%, 59.2% and 73.7% respectively. Their sensitivity in predicting death were 44.4%, 88.9% and 83.3% with a specificity of 87.8%, 54.9% and 68.3% respectively. In both PSI score and IDSA/ATS criteria risk scoring systems, mortality rate, need for ICU admission increased progressively with increasing scores but CURB-65 score did not show this correlation. The PSI class ≥IV was more sensitive in predicting ICU admission than CURB-65 and IDSA/ATS criteria. Conclusions: PSI was most sensitive in both predicting ICU admission and death whereas CURB-65 is most specific in predicting ICU admission and death. But CURB-65 is least sensitive in both predicting ICU admission and death. Even though IDSA/ATS criteria did not have highest sensitivity and specificity as single criteria it had modest sensitivity and specificity in predicting ICU admission and death.